Composition of fecal microbiota in low-set rectal cancer patients treated with FOLFOX - Jing Li; Jingtao Li; Na Lyu; Yue Ma; Fei Liu; Yuqing Feng; Li Yao; Zhiyong Hou; Xiaofeng Song; Hongchuan Zhao; Xiaoya Li; Yingdian Wang; et al. (SAGE Publishing, 2020)
Background: FOLFOX treatment is a method used widely to reduce tumor size in low-set rectal cancer, with variable clinical results. FOLFOX agents comprise a mixture of oxaliplatin and 5-fluorouracil, the efficacy of which might be modulated by the gut microbiome in humans. This study aimed to determine whether the bowel microbiota is a factor that influences FOLFOX treatment. Methods: To investigate the role of gut microbiota during FOLFOX treatment, we carried out comprehensive metagenomic and metabolomic analyses on 62 fecal samples collected from 37 low-set rectal cancer patients. A set of 31 samples was collected before the patients underwent treatment; another 31 samples were obtained after the treatment was completed. Among these samples, 50 were paired samples collected before and after FOLFOX treatment. The patients were divided into responder and nonresponder groups according to the treatment outcome. Metagenomic sequencing was performed on these fecal samples. Diverse bacterial taxa were identified by MetaGeneMark, Soapaligner, and DIAMOND; microbiotal data analyses were carried out in the R environment. Differences in microbial taxa and metagenomic linkage groups were observed in multiple comparative analyses. Results: The gut microbiota was altered after treatment. Compared with before treatment, the changes in bacterial diversity and microbiotal composition after treatment were more apparent in the responder group than in the nonresponder group. Bacterial species analysis revealed a group of gut bacteria in multiple comparisons, with a group of eight specific species being associated with the outcome of FOLFOX treatment. Responders and nonresponders before treatment were clearly separated based on this bacterial subset. Finally, the metagenomic linkage group network and metabolomic analyses based on the genomic data confirmed a more significant change in the gut microbiota during FOLFOX treatment in the responder group than in the nonresponder group. Conclusions: Overall, our results describe a dynamic process of gut microbiotal changes from the start to the end of FOLFOX treatment, and verified a close relationship between microbiota and treatment outcome. Recognition of the significance of microbiotal intervention before FOLFOX treatment for low-set rectal cancer may improve the effects of these agents.